Nutritional strategies to attenuate postprandial glycemic response. (10th June 2022) - Pasmans, Kenneth; Meex, Ruth C. R.; van Loon, Luc J. C.; Blaak, Ellen E.
Summary: Maintaining good glycemic control to prevent complications is crucial in people with type 2 diabetes and in people with prediabetes and in the general population. Different strategies to improve glycemic control involve the prescription of blood glucose‐lowering drugs and the modulation of physical activity and diet. Interestingly, lifestyle intervention may be more effective in lowering hyperglycemia than pharmaceutical intervention. Regulation of postprandial glycemia is complex, but specific nutritional strategies can be applied to attenuate postprandial hyperglycemia. These strategies include reducing total carbohydrate intake, consuming carbohydrates with a lower glycemic index, the addition of or substitution by sweeteners and fibers, using food compounds which delay or inhibit gastric emptying or carbohydrate digestion, and using food compounds which inhibit intestinal glucose absorption. Nevertheless, it must be noted that every individual may respond differently to certain nutritional interventions. Therefore, a personalized approach is of importance to choose the optimal nutritional strategy to improve postprandial glycemia for each individual, but this requires a better understanding of the mechanisms explaining the differential responses between individuals.